Secondary hyperlipidemias: etiology and pathogenesis - A. I. Ershova; D. O. Al Rashi; A. A. Ivanova; Yu. O. Aksenova; A. N. Meshkov (Российский кардиологический журнал, 2019)
In accordance with modern clinical guidelines, the main aim of therapy for cardiovascular risk reducing is achievement of target level of lipid parameters. Some common diseases, medications prescribed in routine clinical practice, as well as dietary disorders can cause the development of lipid metabolism disorders, called secondary hyperlipidemias. Identification and treatment (or elimination) of secondary causes of hyperlipidemia may contribute to the effectiveness of treatment of patients with lipid metabolism disorders. This review presents the underlying conditions and pathogenetic mechanisms responsible for the development of secondary hyperlipidemia.